Health Center Utilization among the Elderly in the East Java Province - Megatsari, Hario; Nandini, Nurhasmadiar; Laksono, Agung Dwi (Universitas Airlangga, 2023)
Background: According to WHO, the elderly is one of the vulnerable groups apart from children and pregnant women. This study aims to analyze the factors related to health center utilization among the elderly in East Java. Methods: This study analyzed secondary data from the Indonesia Basic Health Survey 2018. Using the stratification method and multistage random sampling, this study recruited 25,034 elderly people in East Java as samples. In addition to health center utilization as the dependent variable, residence, age, gender, marriage, education, occupation, socioeconomics, insurance, and travel time to a health center were analyzed as independent variables. Data were analyzed using binary logistic regression. Results: The results found that age was related to health center utilization. Elderly men had 0.874 times more probability than elderly women to use health centers (OR 0.874; 95% CI 0.869-0.879). Marital, education, occupation, and socioeconomic, were also found to be significantly related to health center utilization. The elderly who had health insurance managed by the government had a 1.883 times higher probability than the elderly who did not have health insurance to make use of health center services, while other types of insurance had a lower probability. Based on the travel time to health centers, the elderly who had a travel time of 10 minutes or less were 1.099 times more likely than the elderly who had a travel time of >10 minutes to use health centers (OR 1.099; 95% CI 1.094-1.105). Conclusion: Seven variables had a relationship with health center utilization among the elderly in East Java; age, gender, marriage, education, occupation, insurance, and travel time to health centers. Policymakers can use the research results to determine specific targets to accelerate the increase in health center utilization for the elderly in East Java.